FRI0207 BASELINE LEVELS OF BAFF, APRIL AND CD8+ EFFECTOR MEMORY CELLS AS PREDICTORS OF SLEDAI RESPONSE TO BELIMUMAB THERAPY. (June 2019) - Regola, Francesca; Piantoni, Silvia; Andreoli, Laura; Lowin, Torsten; Kumar, Rajesh; Airò, Paolo; Franceschini, Franco; Tincani, Angela; Pongratz, Georg
Abstract : Background: Systemic lupus erythematosus (SLE) patients show high circulating levels of BLyS (B lymphocyte stimulator, also known as BAFF) and of other cytokines belonging to the tumor necrosis factor (TNF) superfamily [1]. Belimumab is a monoclonal antibody against soluble BLyS used for treatment of refractory SLE. Although B cells are the main target of this therapy, a BLyS-dependent T cell activation pathway has also been demonstrated [2]. Clinical studies showed that high levels of anti-DNA antibodies and low complement at baseline are predictors of response to Belimumab treatment. Objectives: Our study aims at exploring the role of biomarkers belonging to the TNF superfamily and of effector T-lymphocytes as predictors of response. Methods: Twenty-one patients with SLE received Belimumab. Clinical evaluation and laboratory test were performed at baseline and after six and twenty months of therapy. Biomarkers belonging to the TNF superfamily (BAFF, APRIL, sBCMA, sCD40L, sTACI, TWEAK) were tested by high-sensitivity ELISA in all patients and lymphocyte immunophenotyping was performed by flow cytometry in ten subjects. SLE-disease activity was assessed by SLEDAI-2K score. Results: BAFF and APRIL baseline serum levels and the number of CD3+CD8+ effector memory T cells were correlated positively with SLEDAI-2K improvement after 12 months of treatment (Pearson correlation=0.535 (p=0.015), 0.504 (p=0.023) and 0.654 (p=0.040)). After backwards exclusion from linear regression analysis including SLEDAI-2K, effector T cell relative number and BAFF or APRIL at baseline, only APRIL remained as significant independent predictor of SLEDAI-2K improvement after 12 months of therapy (adjusted R square=0.649; p=0.025). Moreover, after comparing TNF-family members serum levels and SLEDAI-2K at baseline, only BAFF showed the best predictive value (adjusted R 0.564, p<0.001). Conclusion: In our cohort of SLE patients, baseline serum level of APRIL together with percentage of CD3+CD8+ effector memory cells, or BAFF serum level alone resulted as best predictors of response to Belimumab. Considering that immunophenotyping is often not done in clinical practice, BAFF baseline serum levels alone could be used routinely as a good predictor of response to therapy, as suggested by post-hoc analyses of the BLISS study and showed by a recent "real-life" observational study [3]. References: [1] Ng LG, et al. J Immunol, 2004 [2] Samy E, et al. Int Rev Immunol, 2017 [3] Parodis I, et al. ACR, 2016 Disclosure of Interests: Francesca Regola: None declared, Silvia Piantoni: None declared, Laura Andreoli: None declared, Torsten Lowin: None declared, Rajesh Kumar : None declared, Paolo Airò: None declared, Franco Franceschini: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Georg Pongratz : None declared